2020
DOI: 10.3389/fpsyg.2020.591498
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the 2016 Copa América Centenario Victory on Social Trust, Self-Transcendent Aspirations and Evaluated Subjective Well-Being: The Role of Identity With the National Team and Collective Pride in Major Sport Events

Abstract: Following a neo-Durkheimian perspective, major sporting events such as the World Cup or the America’s Cup differ from other collective rituals because they promote interest throughout the nation due to their massiveness and international character. In order to increase the scientific knowledge related to these type of rituals, the aim of this study was to observe the effects that the Chilean victory in the 2016 Copa América Centenario had on social variables such as trust, self-transcendent aspirations, and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 81 publications
(144 reference statements)
0
12
0
Order By: Relevance
“…Group-based pride reflects the positive evaluation of individuals to the status or achievement of their group. Existing studies have suggested that group-based pride originates from the consideration of the ingroup as moral (Leach et al, 2007), as having a legitimate advantage over outgroups (Harth et al, 2008), or as succeeding in a match (Bravo et al, 2020). As discussed earlier, we anticipate that when a team leader engages in identity leadership, team members will internalize their group membership and view their ingroup as a valued and positive social group, in turn, elicits group-based pride.…”
Section: Identity Leadership and Group-based Pridementioning
confidence: 85%
“…Group-based pride reflects the positive evaluation of individuals to the status or achievement of their group. Existing studies have suggested that group-based pride originates from the consideration of the ingroup as moral (Leach et al, 2007), as having a legitimate advantage over outgroups (Harth et al, 2008), or as succeeding in a match (Bravo et al, 2020). As discussed earlier, we anticipate that when a team leader engages in identity leadership, team members will internalize their group membership and view their ingroup as a valued and positive social group, in turn, elicits group-based pride.…”
Section: Identity Leadership and Group-based Pridementioning
confidence: 85%
“…Most research on group-pride has presented group-pride as “a feeling of pride for group achievements,” without specifying whether the experience of pride is similar to the experience of self-pride. Few studies have mentioned that experiences of group-pride include feeling associated with or experiencing a sharedness with or intimacy with others ( Sullivan, 2013 ; Delvaux et al, 2016 ; Bravo et al, 2020 ). Therefore, the present research will examine whether group-pride can be distinguished from the other forms of pride on feelings of closeness.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…All three experiments examined feelings of pride and feelings of being responsible for the achievement following these manipulations. Following the suggestions that all forms of pride would motivate people ( Williams and Davies, 2017 ), that especially self-pride would relate to increased status ( Griskevicius et al, 2010 ; Bollo et al, 2018 ; Septianto et al, 2018 ), and that especially other-oriented forms of pride would relate to increased closeness to others ( Delvaux et al, 2016 ; Williams and Davies, 2017 ; Bravo et al, 2020 ) and increased admiration for others ( Williams, 2018 ; Watkins and Bastian, 2019 ), Experiment 1 examined the motivation of people, their felt status, change in closeness to others, and admiration following the three forms of pride. Experiments 2 and 3 more closely examined the interplay of the self and others and the tendencies to inflate or deflate oneself or others following the different forms of pride and studied whether the experiences of people when it comes to self- and other-inflation, of distancing and approaching and of other-appreciation and -devaluation were affected differently by the different forms of pride.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations